Modern state, problems and prospects of development of Odesa recreational complex - Kudelina, S.; Hetmanenko, A.; Nikolaieva, O.; Khomutov, V. (Journal of Education, Health and Sport, 2023)
The article is devoted to the socio-geographical characteristics of the territorial recreational complex of Odesa. The article gives a historical review of establishment and development of recreational activity, gives a description of natural recreational resources and historical and cultural potential of the city. It gives a description of certain types of recreational activities, in particular, sanatorium treatment, medical rehabilitation and tourism, resort areas, formed within the city limits, the problems and prospects of development of Odesa recreational complex are considered here.